1999
DOI: 10.1046/j.1365-313x.1999.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequences within both the N‐ and C‐terminal domains of phytochrome A are required for PFR ubiquitination and degradation

Abstract: SummaryPhotoconversion of the plant photoreceptor phytochrome A (phyA) from its inactive Pr form to its biologically active Pfr form initiates its rapid proteolysis. Previous kinetic and biochemical studies implicated a role for the ubiquitin/26S proteasome pathway in this breakdown and suggested that multiple domains within the chromoprotein are involved. To further resolve the essential residues, we constructed a series of mutant PHY genes in vitro and analyzed the Pfr-specific degradation of the resulting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 58 publications
6
57
0
1
Order By: Relevance
“…Therefore, we conclude that the loss of PHYA-associated FITC labeling under cR light resulted from enhanced degradation of the apoprotein. These observations are consistent with studies on oat, in which phytochrome also became gradually undetectable by immunostaining during cR irradiation (Mackenzie et al, 1978), and with many previous reports of FR light-absorbing phytochrome (Pfr)-specific degradation of PhyA (Clough et al, 1999). However, the site at which PHYA is degraded is still not determined.…”
Section: Light-regulated Nuclear Import Of Phytochromessupporting
confidence: 81%
“…Therefore, we conclude that the loss of PHYA-associated FITC labeling under cR light resulted from enhanced degradation of the apoprotein. These observations are consistent with studies on oat, in which phytochrome also became gradually undetectable by immunostaining during cR irradiation (Mackenzie et al, 1978), and with many previous reports of FR light-absorbing phytochrome (Pfr)-specific degradation of PhyA (Clough et al, 1999). However, the site at which PHYA is degraded is still not determined.…”
Section: Light-regulated Nuclear Import Of Phytochromessupporting
confidence: 81%
“…Lysine 206 of Arabidopsis phyA is the main ubiquitination site The N-terminal domain of phyA has been shown to be ubiquitinated and degraded as a result of the biochemical response to light (31,32). Identification of ubiquitination site can be accomplished by either direct analysis of ubiquitinated proteins by mass spectrometry (MS) or protein degradation analysis using lysine mutated proteins (34,35).…”
Section: Resultsmentioning
confidence: 99%
“…COP1 have been identified as E3 ligases in the proteasome pathway, which with CUL1 is involved in phyA degradation under different growth media conditions (29,30). To define specific ubiquinated lysines in phyA, C-terminal conserved lysines within the region required for Pfr signal transduction of oat phyA were replaced with arginines but these mutant phyA proteins showed the same degradation kinetics as wild-type phyA (31). Recent phyA functional studies showed that the N-terminal domain of phyA is important for ubiquitination and degradation (25,31,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations